Draft Genome Sequence of Lactobacillus reuteri 121, a Source of α-Glucan and β-Fructan Exopolysaccharides - Gangoiti, Joana (Genome Announc, 2017)
The probiotic bacterium Lactobacillus reuteri 121 is a well-known producer of diverse homoexopolysaccharides (α-glucans and β-fructans) from sucrose and maltodextrins/starches of interest for food applications. Here, we report the draft genome sequence of this strain, with a focus on carbohydrate-active enzymes.